Réponses

2014-08-25T13:26:38+02:00
3a+7 = 34
3a = 27
a = 9

-3-2a=7
-2a = 10
a = -5

5-2a=12
-2a = 7
a = -7/2
2014-08-25T13:48:45+02:00
Résoudre les équations suivantesa)     3a + 7 = 34
  ⇔  3a + 7 - 7 = 34 - 7
  ⇔  3a  = 27  
  ⇔  3a × ( 1 / 3 ) = 27 × ( 1 / 3 )
  ⇔  a  = 27 / 3
  ⇔  a  = 9

b)     -3 - 2a = 7
  ⇔  -3 - 2a + 3 = 7 + 3
  ⇔   - 2a  = 10
  ⇔   - 2a × ( - 1/2 ) = 10 × ( - 1/2 )
  ⇔     a  = -5

c)       5 - 2a = 12
  ⇔   5 - 2a - 5 = 12 - 5
  ⇔   - 2a  = 7
  ⇔   - 2a × ( - 1/2 ) = 7 × ( - 1/2 )
  ⇔     a  = -7 / 2